Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru Honorer di SMA Negeri 3 Halmahera Selatan - Hi Mustafa, Irfandi R.; Ihsan, Ikhlashul; Apling, Mujais; Muhammad, Ardiyana (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine the leadership of school principals in improving the performance of honorary teachers and what the supporting and inhibiting factors are. This research uses a qualitative descriptive approach with the research subjects namely the principal and teacher council at SMA Negeri 3 South Halmahera. Data collection techniques used in research are observation, interviews and documentation. The results of the research show that the principal always provides guidance in terms of involving teachers in activities and training, supervising monitoring and monitoring in each class, carrying out supervision, as well as providing motivation and providing ideas and thoughts to teachers in improving the performance of honorary teachers at SMA Negeri 3 South Halmahera very good.